Transformation of (+/-)-lavandulol and (+/-)-tetrahydrolavandulol by a fungal strain Rhizopus oryzae - Daramwar, Pankaj P.; Rincy, Raju; Niloferjahan, Siddiqui; Krithika, Ramakrishnan; Gulati, Arvind; Yadav, Amit; Sharma, Rakesh; Thulasiram, Hirekodathakallu V. (Bioresource Technology, 2012)
Biotransformation of an irregular monoterpene alcohol, (+/-)-lavandulol [(+/-)-5-methyl-2-(1-methylethenyl)-4-hexen-1-ol] (I) and its tetrahydro derivative, (+/-)-tetrahydrolavandulol [(+/-)-2-isopropyl-5-methylhexan-1-ol] (II) were studied using a soil isolated fungal strain Rhizopus oryzae. Five metabolites, 2-((3,3-dimethyloxiran-2-yl)methyl)-3-methylbut-3-en-1-ol (Ia), 2-methyl-5-(prop-1-en-2-yl)hex-2ene-1,6-diol (Ib), 2-methyl-5-(prop-1-en-2-yl)hexane-1,6-diol (Ic), 2-(3-methylbut-2-enyl)-3-methylenebutane-1,4-diol (Id), 5-methyl-2-(2-methyloxiran-2-yl)hex-4-en-1-01 (Ie) have been isolated from the fermentation medium and characterized with lavandulol as a substrate. When tetrahydrolavandulol used as a substrate, two metabolites 2-isopropyl-5-methylhexane-1,5-diol (IIa) and 2-isopentyl-3-methylbutane-1,3-diol (lib) have been isolated from the fermentation medium. Biotransformation studies with R. oryzae clearly indicate that the organism initiates the transformation either by hydroxylation at allylic methyl groups or epoxidation of double bond. GC and GCMS analyses indicated that both (R)and (S)-enantiomers of I and II have been transformed into corresponding hydroxylated or epoxy derivatives, when racemic I and II were used as substrates. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biotransformation; Fungus; Lavandulol; Rhizopus oryzae; Tetrahydrolavandulol

Characterization of 10-hydroxygeraniol dehydrogenase from catharanthus roseus reveals cascaded enzymatic activity in iridoid biosynthesis - Krithika, Ramakrishnan; Srivastava, Prabhakar Lal; Rani, Bajaj; Kolet, Swati P.; Chopade, Manojkumar; Soniya, Mantri; Thulasiram, Hirekodathakallu V. (Scientific Reports, 2015)
Catharanthus roseus [L.] is a major source of the monoterpene indole alkaloids (MIAs), which are of significant interest due to their therapeutic value. These molecules are formed through an intermediate, cis-trans-nepetalactol, a cyclized product of 10-oxogeranial. One of the key enzymes involved in the biosynthesis of MIAs is an NAD(P)(+) dependent oxidoreductase system, 10-hydroxygeraniol dehydrogenase (Cr10HGO), which catalyses the formation of 10-oxogeranial from 10-hydroxygeraniol via 10-oxogeraniol or 10-hydroxygeranial. This work describes the cloning and functional characterization of Cr10HGO from C. roseus and its role in the iridoid biosynthesis. Substrate specificity studies indicated that, Cr10HGO has good activity on substrates such as 10-hydroxygeraniol, 10-oxogeraniol or 10-hydroxygeranial over monohydroxy linear terpene derivatives. Further it was observed that incubation of 10-hydroxygeraniol with Cr10HGO and iridoid synthase (CrIDS) in the presence of NADP(+) yielded a major metabolite, which was characterized as (1R, 4aS, 7S, 7aR)-nepetalactol by comparing its retention time, mass fragmentation pattern, and co-injection studies with that of the synthesized compound. These results indicate that there is concerted activity of Cr10HGO with iridoid synthase in the formation of (1R, 4aS, 7S, 7aR)-nepetalactol, an important intermediate in iridoid biosynthesis.

Functional characterization of novel sesquiterpene synthases from Indian sandalwood, santalum album - Srivastava, Prabhakar Lal; Daramwar, Pankaj P.; Krithika, Ramakrishnan; Pandreka, Avinash; Shankar, S. Shiva; Thulasiram, Hirekodathakallu V. (Scientific Reports, 2015)
Indian Sandalwood, Santalum album L. is highly valued for its fragrant heartwood oil and is dominated by a blend of sesquiterpenes. Sesquiterpenes are formed through cyclization of farnesyl diphosphate (FPP), catalyzed by metal dependent terpene cyclases. This report describes the cloning and functional characterization of five genes, which encode two sesquisabinene synthases (SaSQS1, SaSQS2), bisabolene synthase (SaBS), santalene synthase (SaSS) and farnesyl diphosphate synthase (SaFDS) using the transcriptome sequencing of S. album. Using Illumina next generation sequencing, 33.32 million high quality raw reads were generated, which were assembled into 84,094 unigenes with an average length of 494.17 bp. Based on the transcriptome sequencing, five sesquiterpene synthases SaFDS, SaSQS1, SaSQS2, SaBS and SaSS involved in the biosynthesis of FPP, sesquisabinene, beta-bisabolene and santalenes, respectively, were cloned and functionally characterized. Novel sesquiterpene synthases (SaSQS1 and SaSQS2) were characterized as isoforms of sesquisabinene synthase with varying kinetic parameters and expression levels. Furthermore, the feasibility of microbial production of sesquisabinene from both the unigenes, SaSQS1 and SaSQS2 in non-optimized bacterial cell for the preparative scale production of sesquisabinene has been demonstrated. These results may pave the way for in vivo production of sandalwood sesquiterpenes in genetically tractable heterologous systems.